Areca catechu—From farm to food and biomedical applications. (11th March 2020) - Salehi, Bahare; Konovalov, Dmitry A.; Fru, Pascaline; Kapewangolo, Petrina; Peron, Gregorio; Ksenija, Mileski S.; Cardoso, Susana M.; Pereira, Olivia R.; Nigam, Manisha; Nicola, Silvana; Pignata, Giuseppe; Rapposelli, Simona; et al.
Abstract : The family Arecaceae includes 181 genera and 2, 600 species with a high diversity in physical characteristics. Areca plants, commonly palms, which are able to grow in nearly every type of habitat, prefer tropical and subtropical climates. The most studied species Areca catechu L. contains phytochemicals as phenolics and alkaloids with biological properties. The phenolics are mainly distributed in roots followed by fresh unripe fruits, leaves, spikes, and veins, while the contents of alkaloids are in the order of roots, fresh unripe fruits, spikes, leaves, and veins. This species has been reputed to provide health effects on the cardiovascular, respiratory, nervous, metabolic, gastrointestinal, and reproductive systems. However, in many developing countries, quid from this species has been associated with side effects, which include the destruction of the teeth, impairment of oral hygiene, bronchial asthma, or oral cancer. Despite these side effects, which are also mentioned in this work, the present review collects the main results of biological properties of the phytochemicals in A. catechu . This study emphasizes the in vitro and in vivo antioxidant, antimicrobial, anticancer, and clinical effectiveness in humans. In this sense, A. catechu have demonstrated effectiveness in several reports through in vitro and in vivo experiments on disorders such as antimicrobial, antioxidant, or anticancer. Moreover, our findings demonstrate that this species presents clinical effectiveness on neurological disorders. Hence, A. catechu extracts could be used as a bioactive ingredient for functional food, nutraceuticals, or cosmeceuticals. However, further studies, especially extensive and comprehensive clinical trials, are recommended for the use of Areca in the treatment of diseases.